Serum Levels of S100A11 and MMP-9 in Patients with Epithelial Ovarian Cancer and Their Clinical Significance - Li, Wenjing (Biomed Res Int, 2021)
OBJECTIVE: To investigate the serum levels of calgizzarin (S100A11) and matrix metalloproteinase-9 (MMP9) in patients with epithelial ovarian cancer (EOC) and determine their clinical significance. METHODS: Serum levels of S100A11 and MMP9 were detected in patients with EOC, patients with benign ovarian tumor, and healthy women. The correlation between the two markers and clinicopathological characteristics of ovarian cancer was analysed. RESULTS: The serum levels of S100A11 and MMP-9 in patients with EOC were higher than those in patients with benign ovarian tumor and in healthy women, and the expression levels of S100A11 and MMP-9 were positively correlated. S100A11 and MMP-9 were correlated with tumor staging, postoperative residual foci, ascites volume, serum CA125 level, chemotherapy response, and lymph node metastasis, while S100A11 and MMP-9 were not associated with the bilevel classification, histological type, age, and degree of differentiation. CONCLUSION: S100A11 and MMP-9 were both highly expressed in the serum of patients with EOC and were associated with cancer development, invasion, and metastasis. Therefore, they can be used as an important reference maker in the diagnosis and treatment of ovarian cancer.